What attracts human capital? Understanding the skill composition of interregional job matches in Germany - Melanie Arntz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
By examining the destination choice patterns of heterogenous labor, this paper tries to explain the skill composition of internal job matching flows in Germany. Estimates from a nested logit model of destination choice suggest that spatial job matching patterns by high-skilled individuals are mainly driven by interregional income differentials, while interregional job matches by less-skilled individuals are much more affected by regional differentials in job opportunities. Regional differentials in non-pecuniary assets slightly contribute to spatial sorting processes in Germany. Such differences in destination choices by skill level are partly modified by different spatial patterns of job-to-job matches and job matches after unemployment. Simulating job matching patterns in a scenario of economic convergence between eastern and western Germany demonstrates that wage convergence is the most effective means of attracting human capital to eastern Germany.
Keywords: C35; J61; R23; 330; interregional job matches; destination choice; human capital